2015
DOI: 10.11591/ijece.v5i5.pp1075-1082
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Three PID Controller Tuning Algorithm on a Process Plant

Abstract: Accurate tuning of controller in industrial process operation is prerequisite to system smooth operation which directly reduce process variability, improved efficiency, reduced energy costs, and increased production rates. Performance evaluation of a model based PID controller tuning algorithm on a chemical process plant is presented in this paper. The control action of three different PID controller tuning algorithms namely; Hagglund-Astrom, Cohen and Coon, and Ziegler-Nichols on the process plant was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
(3 reference statements)
0
7
0
1
Order By: Relevance
“…Then, two control schemes with modified Smith predictor for first order process with dead time [8] are explained. These control schemes use PID/PI (proportional integral derivative/ proportional integral) Controller [9,10] as it is feasible and easy to implement. All the schemes are simulated using Simulink/Matlab software.…”
Section: Methodsmentioning
confidence: 99%
“…Then, two control schemes with modified Smith predictor for first order process with dead time [8] are explained. These control schemes use PID/PI (proportional integral derivative/ proportional integral) Controller [9,10] as it is feasible and easy to implement. All the schemes are simulated using Simulink/Matlab software.…”
Section: Methodsmentioning
confidence: 99%
“…To design a digital controller by direct digital design method, first, it needs to transform continuoustime model of ACFC into Discrete time Model [14] and then need to design a digital controller directly in the digital domain by using matched pole zero method. With the help of matched pole-zero method continuous model of ACFC is transformed in to digital form.The Discrete-time Transfer functions of ACFC are shown in (13)(14)(15)(16)(17)(18)). The designed discrete-time model of ACFC is very suitable to design the digital controller directly by using Root locus technique.…”
Section: Direct Digital Design Methodsmentioning
confidence: 99%
“…From the above results, it is observed that we are able to get zero voltage regulation but again to improve performance of the converter two loop controllers are required [15][16][17]. Authors are presented a paper [15] to design a two loop controller for Forward Converter with the active clamp circuit.…”
Section: Two-loop Controllermentioning
confidence: 99%
“…AI techniques such as fuzzy logic , neural networks neural-fuzzy logic have been widely used to proper tuning of PID controller parameters [2]- [4]. Tuning of PID controller parameters in off line made easy with the advent of heuristic optimization techniques [5]- [7]. Genetic Algorithms and Particle swarm Optimization are very popularly used random search heuristic optimization techniques for tuning PID controller parameters [6], [8].…”
Section: Introductionmentioning
confidence: 99%